Extended spectrum beta lactamase producing Escherichia coli eustachian valve infective endocarditis. (September 2021) - Ireifej, Branden; Song, David; Mukuntharaj, Pradeeksha; Seen, Tasur; Almas, Talal; Lin, XiongBin; Kanawati, M. Ali; Sattar, Yasar
Abstract: Endocarditis is an infection of the endocardium caused by a multitude of bacteria, including S. aureus, viridans streptococci, S. bovis, or S. epidermidis, among others. It can cause a variety of physical findings, including new onset murmur, Osler nodes, and Janeway lesions. Endocarditis is diagnosed with multiple positive blood cultures with transesophageal echocardiogram (TEE) showing valvular vegetations. In this article, we present a 47 year old female with a history of ESRD on dialysis who presented with a bleeding fistula found to be in septic shock. Diagnosis of eustachian valve endocarditis with E. Coli ESBL was made through positive blood cultures as well as using TEE. She was started on IV meropenem for seven days, to which the patient completed and eventually was discharged home with resolution of symptoms. Highlights: ● There are only a few case reports in literature on E. Coli ESBL induced Eustachian valve endocarditis, which makes it an extremely rare presentation or a frequently unnoticed condition ● The diagnosis of endocarditis is made through Duke's criteria where you have positive blood cultures and echocardiogram revealing vegetation ● Persistent E. coli bacteremia in elderly in the absence of cardiac risk factors while on appropriate antibiotic therapy should consider E. Coli ESBL induced Eustachian valve endocarditis as a differential